Assessment of the Understanding of Medical Ethics Subject among Anbar Medical Group Students (Medico Legal Update, 2020)
Background: Future doctors and medical students are expected to learn about the important moral ethical communication with their patients and health care personnel.Objectives: The study aimed to have opinion of medical students on medical ethics education.Methodology: Cross sectional study carried out in both medicine and pharmacy colleges of at Anbar University for a period extended from 4th of November 2018 till the 28th of May 2019. The study was conducted on total sample size of 211 both males and females in medical and pharmacist students at Anbar University who age group ranging from 20-24 years old.Results: About 86.3% of students under study believe that medical ethics subject is important in the curriculum of medical group colleges so as to learn basic knowledge of attitude (47.8%), and about 48% have the opinion of taking such subject in the first/second year of college. At the same time, 45.6% of students believe that the subject is boring and patient communication lecture was the highest percentage (47.9%) chosen by students as the most important item among the medical ethics subject.Conclusion: Low perception and knowledge about the importance of medical ethics subject among medical group students in their near future career.